Comparison of endoscopic vacuum therapy versus endoscopic stenting for esophageal leaks: systematic review and meta-analysis. Issue Volume 31:Issue11(2018) (25th June 2018) - Rausa, E; Asti, E; Aiolfi, A; Bianco, F; Bonitta, G; Bonavina, L
SUMMARY: Esophageal leaks remain a life-threatening postoperative complication of esophagectomy. Currently, self-expanding metal stents (SEMS) represent the endoscopic mainstay of treatment. Recently, endoscopic vacuum therapy (EVT) has emerged and shown promising results in these patients. We conducted an electronic systematic search using MEDLINE databases (PubMed, EMBASE, and Web of Science) looking for studies comparing EVT and SEMS for the treatment of esophageal leak and/or perforation. Four studies including 163 patients matched the inclusion criteria. Esophageal leak closure rate is significantly higher with EVT than SEMS [pooled odds ratio 5.51 (95% CI 2.11–14.88; P < 0.001)]. Additionally, EVT has a shorter treatment duration [pooled mean difference −9.0 days (95% CI 16.6–1.4; P = 0.021)], lower major complication ( P = 0.011), and in-hospital mortality ( P = 0.002) rate compared to SEMS. EVT for esophageal leak is feasible and safe. It has the potential to become the new gold standard in the endoscopic treatment of esophageal leaks and perforations. However, further comparative studies with SEMS are needed to strengthen the current evidence.